Motivation and success factors in radiological research in Germany – results of a survey by the Methodology and Research Working Group of the German Radiological Society - Wegner, Franz; Heinrichs, Helen; Stahlmann, Katharina; Molwitz, Isabel; Keller-Yamamura, Sarah; Kloeckner, Roman; Barkhausen, Jörg; Bäuerle, Tobias; Cyran, Clemens C.; Dietzel, Matthias; Eisenblätter, Michel; Hilger, Ingrid; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Purpose Investigation of motivation and identification of success factors in radiology research in Germany. Materials and Methods Using a German online survey (54 questions, period: 3.5 months), demographic aspects, intrinsic and extrinsic success characteristics, as well as personal and organizational success factors were surveyed based on a career success model. The survey results were reported descriptively. The correlations between success factors and success characteristics were examined using linear, binary-logistic, and multinomial regression models. Results 176 people (164 academically active, 10 not academically active) answered the survey. Most participants (80%, 139/174) worked at a university hospital. 32% had privatdozent or professor as their highest academic title (56/173). The researchers' main motivation was intrinsic interest in research (55%, 89/163), followed by a desire to increase their own career opportunities (25%, 41/163). The following were identified as factors for intrinsic success: i) support from department management (estimate=β=0.26, p<0.001), ii) good work-life balance (β=0.37, p<0.001), and iii) the willingness to pursue science even after reaching the career goal (β=0.16, p<0.016). Relevant factors for extrinsic scientific success were mentoring, protected research time, and activities in professional societies. Conclusion Researchers in German radiology are mainly intrinsically motivated. Factors known from the literature that determine intrinsic and extrinsic scientific success were confirmed in this study. Knowledge of these factors allows targeted systematic support and could thus increase scientific success in German radiology. Key Points Main motivation for German radiology research is intrinsic interest, followed by career opportunities. Factors for intrinsic scientific success are good work-life balance and support by department management. Factors for extrinsic scientific success are mentoring, activities in professional societies, and protected research time. Citation Format Wegner F, Heinrichs H, Stahlmann K et al. Motivation and success factors in radiological research in Germany - results of a survey by the Methodology and Research Working Group of the German Radiological Society. Fortschr Röntgenstr 2024; DOI 10.1055/a-2350-0023
CRIS-Team Scopus Importer:2024-08-16
Keywords: radiological research; scientific success; success factors; survey